Is Heading in Youth Soccer Dangerous Play?. Issue 2 (2nd April 2016) - O'Kane, John W.
ABSTRACT: Background : Soccer is among the most popular youth sports with over 3 million youth players registered in the U.S. Soccer is unique in that players intentionally use their head to strike the ball, leading to concerns that heading could cause acute or chronic brain injury, especially in the immature brains of children. Methods : Pub Med search without date restriction was conducted in November 2014 and August 2015 using the terms soccer and concussion, heading and concussion, and youth soccer and concussion. 310 articles were identified and reviewed for applicable content specifically relating to youth athletes, heading, and/or acute or chronic brain injury from soccer. Results : Soccer is a low-risk sport for catastrophic head injury, but concussions are relatively common and heading often plays a role. At all levels of play, concussions are more likely to occur in the act of heading than with other facets of the game. While concussion from heading the ball without other contact to the head appears rare in adult players, some data suggests children are more susceptible to concussion from heading primarily in game situations. Contributing factors include biomechanical forces, less developed technique, and the immature brain's susceptibility to injury. Conclusions : There is no evidence that heading in youth soccer causes any permanent brain injury and there is limited evidence that heading in youth soccer can cause concussion. A reasonable approach based on U.S. Youth Soccer recommendations is to teach heading after age 10 in controlled settings, and heading in games should be delayed until skill acquisition and physical maturity allow the youth player to head correctly with confidence.